Sexuality & gender for mental health professionals : a practical guide - Richards, Christina; Barker, Meg-John, 1974- (Los Angeles ; SAGE, 2013)
Examines the complexities of sexuality and gender, detailing the common and many of the less common sexualities, genders, and relationship forms, and explains experiences and issues relating to each.
Transgender (Trans) : living a different gender from that assigned at birth -- Intersex/diversity of sexual development (DSD) -- Cisgender : living in the gender assigned at birth -- Further genders -- Bondage and discipline, dominance and submission, and sadomasochism (BDSM)/Kink -- Asexuality -- Bisexuality -- Lesbian and gay sexuality -- Heterosexuality -- Cross-dressing -- Further sexualities -- Monogamy -- Non-monogamy.
Includes bibliographical references and index.
Keywords: Sex (Psychology); Sexual Behavior -- psychology; Transgender Persons -- psychology; Sex (Psychology)